Graphical history list on world wide web visualisation: A usability paradigm - Mehta, Sejal Jitendra; Seong, Daniel Su Kuen (2006)
The World Wide Web (WWW) is a fast emerging technology which enables users to view the information via a web browser such as Internet Explorer and Netscape Navigator.Studies have revealed that users often get ‘lost’ as they navigate deeper and deeper.Information visualisation is adopted by many researchers to construct the graphical representation of history list as text-based imposes a burden on users. Although information visualisation is a useful tool, questions arise on its usability and human short term memory.A prototype of a graphical history list is developed while taking the usability and human short term memory into considerations.The research results have significantly indicated a positive and promising outcome on a usable graphical history list on WWW visualisation.